Quantitative diagnosis of HER2 protein expressing breast cancer by single‐particle quantum dot imaging. (26th September 2016) - Miyashita, Minoru; Gonda, Kohsuke; Tada, Hiroshi; Watanabe, Mika; Kitamura, Narufumi; Kamei, Takashi; Sasano, Hironobu; Ishida, Takanori; Ohuchi, Noriaki
Abstract: Overexpression of HER2 is one of the major causes of breast cancer, and therefore precise diagnosis of its protein expression level is important. However, current methods estimating the HER2‐expression level are insufficient due to problem with the lack of quantification. This might result in a gap between diagnostics and therapeutics targeting HER2. Therefore, a new effective diagnostic method is needed. We developed a new immunohistochemical (IHC) technique with quantum dots (QD)‐conjugated trastuzumab using single‐particle imaging to quantitatively measure the HER2 expression level. Tissues from 37 breast cancer patients with available detailed clinical information were tested by IHC with QDs (IHC‐QD) and the correlation with IHC with 3, 3′‐diaminobenzidine (DAB), fluorescence in situ hybridization (FISH), and IHC‐QD was examined. The number of QD‐conjugated trastuzumab particles binding specifically to a cancer cell was precisely calculated as the IHC‐QD score. The IHC‐QD score in 37 cases was correlated proportionally with the score of HER2 gene copy number as assessed by FISH ( R = 0.83). When HER2 positivity was judged to be positive, the IHC‐QD score with our cut‐off level was exactly concordant with the FISH score with a cut‐off value of 2.0. Furthermore, IHC‐QDs score and time to progression (TTP) of trastuzumab therapy were well correlated in HER2‐positive cases ( R = 0.69). Conversely, the correlation between FISH score and TTP was not observed. We developed a precisely quantitative IHC method using trastuzumab‐conjugated QDs and single‐particle imaging analysis and propose the possibility of using IHC‐QDs score as a predictive factor for trastuzumab therapy. Abstract : Overexpression of human epidermal growth factor receptor 2 (HER2) is a major cause of breast cancer, and therefore precise diagnosis of its protein expression level is important. We developed a new immunohistochemical technique with quantum dot‐conjugated anti‐HER2 antibody using single‐particle imaging. The quantitative diagnosis of HER2‐expression level was strongly related to its gene amplification, and analysis correlating both factors suggested that the immunohistochemical score is a strong predictive factor for therapy.